Sphyrospermum grandiflorum (Ericaceae: Vaccinieae): a new epiphytic shrub from south eastern Ecuador - Cornejo, Xavier; Pedraza-Peñalosa, Paola (Phytotaxa, 2019)
A new morphologically distinct species of Ericaceae (Vaccinieae) is here described and illustrated. Sphyrospermum grandiflorum, is an epiphytic shrub endemic to the environs of Cordillera del Cóndor, in southeastern Ecuador. It is characterized by its large yellow flowers.